The relationship between shyness and depression: the multiple mediating roles of sense of security and adaptability - Wang, Yuxia; Zhang, Jiayan; Cong, Yixiu (Frontiers in Psychology, 2026)
The overall prevalence of depression among Chinese college students has currently reached 28.4% and continues to rise annually. However, most current research focuses on adolescents, with less attention given to depression among college students. According to the diathesis-stress model, depression results from both individual vulnerability factors and stressful events. Therefore, this study aims to investigate college students (Mage = 19.82, SD = 0.98; Female: 76.8%) through a questionnaire method and analyze the potential mechanisms linking shyness, sense of security, adaptability, and depression using a multiple mediation model. The study found that: (1) shyness significantly and positively predicted depression; (2) sense of security mediated the relationship between shyness and depression; (3) adaptability mediated the relationship between shyness and depression; (4) sense of security and adaptability jointly mediated the relationship between shyness and depression. This study reveals the mechanisms linking shyness to depression in college students, specifically the mediating roles of sense of security and adaptability. This not only enriches the diathesis-stress model but also offers new insights into reducing depression among college students.